An ESP Needs Analysis: Addressing the Needs of English for Informatics Engineering: Analisis Kebutuhan ESP: Mengatasi Kebutuhan Bahasa Inggris untuk Teknik Informatika - Nimasari, Elok Putri (Universitas Muhammadiyah Sidoarjo, 2018)
English for specific purposes (ESP) have different needs of English language use. These needs will be the fundamental indicators to develop appropriate ESP syllabus. In order to find those needs, a need analysis research is necessary to conduct. This qualitative study addresses the result of ESP needs analysis for 95 Informatics Engineering of Muhammadiyah University of Ponorogo students. Brief reviews of ESP, needs analysis, and current learners’ situation of ESP classroom for Informatics Engineering are described as theoretical frameworks. A needs analysis questionnaire is utilized as an approach to find specific needs and to evaluate the current class situation. The results address 10 areas of English language use for Informatics Engineering major.